Effect of rumen-protected fat on in vitro rumen fermentation and apparent biohydrogenation of fatty acids - Behan, A. A.; Chwen, L. T.; Kaka, U.; Muhammad, A. I.; Samsudin, A. A. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
This study aimed to evaluate the effects of rumen-protected fat (RPF) on in vitro fermentation profiles and biohydrogenation of fatty acids. The treatment diets were basal diet (70:30 concentrate to rice straw) with no RPF (CON), basal diet plus prilled fat (PF), basal diet plus prilled fat with lecithin (PFL) and basal diet plus calcium soap of palm fatty acids (CaS). In vitro gas production, fermentation kinetics, in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD), metabolizable energy (ME), rumen fermentation and fatty acid profile were determined. The results show that RPF did not affect cumulative gas production and gas production kinetics. PFL significantly (p < 0.05) improved IVDMD and IVOMD, although the addition of RPF did not affect ME. The volatile fatty acid (VFA), pH, ammonia nitrogen, methane, and molar proportion of VFA were not significantly influenced by the RPF; methane was numerically reduced because of PFL treatment. The concentration of monounsaturated and polyunsaturated fatty acids increased (p < 0.05) whereas that of saturated fatty acids decreased in the control diet. The biohydrogenation of C18:2n-6 and C18 unsaturated fatty acids was enhanced (p < 0.05) by PFL. These findings suggest that PFL enhances gas production, decreases methane and increases the biohydrogenation of C18:2n6 without disrupting rumen fermentation.